Sphingolipids in Disease - Gulbins, Erich.; Petrache, Irina. (Handbook of Experimental Pharmacology, 2013)
Sphingolipids are lipid components of the plasma membrane of eukaryotic cells with an important function in signaling mechanisms in the cell. This book provides insight into the physiological and pathophysiological role of sphingolipids and in particular its derivative ceramide. The function of Sphingolipids in cell signaling with regard to infectious and lung diseases, cancer, cardiovascular diseases and neuropsychiatric disorders are described and treated in distinct parts. Together with Volume 215 from the same Editors, the collection represents a unique, comprehensive work on Sphingolipids, providing information on both: Sphingolipid basic biology as well as its important function in a (patho)physiological context. The book is written for scientists in pharmacology, biochemistry and cell biology with a focus on biomedical research as well as for clinicians in pharmacology, oncology, cardiology, neurology and infectious disease.